Legal nature of administrative-tort procedural relations - Pavlovska, Natalia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article examines the systematic study of administrative-tort procedural relations, specifies their theoretical and applied legal basis. On the basis of the given scientific points of view concerning the maintenance of administrative-tort relations the legal nature and features are defined.The study of the legal nature of administrative-tort procedural relations allowed the author to summarize the accumulated scientific information and results of judicial practice and offer on their basis scientific and practical proposals and recommendations for improving their legal regulation, eliminating existing gaps and conflicts, and identifies areas for further development.The author notes that in polemical form modern scholars-administrators discuss certain rules governing proceedings in cases of administrative offenses (torts), the content of which contributes to new issues, both in theory and in law enforcement. In this regard, there is an objective need for clearer regulation of the rules of proceedings in cases of administrative offenses (torts), which does not allow arbitrary interpretation of the rules.In the context of studying the administrative legislation of Ukraine, the definition of "administrative tort law" as a set of rules governing relations arising in connection with the commission of an administrative offense (tort) has already been formed and improved. Norms of administrative tort law perform the function of protecting law and order, rights and freedoms of citizens. The scope of its legal regulation includes, on the one hand, relations related to the behavior of subjects of administrative law, and on the other hand, the activities of competent authorities to terminate and investigate acts of jurisdictional proceedings on administrative offenses (torts).In this sense, the author's justification for the development of an independent sub-branch of administrative law and administrative process in the form of administrative tort law and administrative tort law, the subject of which are administrative legal relations related to the consideration and opening of administrative offenses.